2004
DOI: 10.1007/s10340-003-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the population frequency of insects and mites causing galls on the leaves of the sycamore maple Acer pseudoplatanus L. in southern Poland

Abstract: Species composition of galls on the leaves of Acer pseudoplatanus L. was analysed in 2002 in three localities: the Wolski Forest, near an urban agglomeration of Krako´w, the Ojco´w National Park and the Andrycho´w Forest District. A total of 12,013 galls were found. The galls were caused by six insect or mite species. The species composition of the galls was identical in the three localities. Artacris cephaloneus (Nalepa) was the most abundant species. The index of occurrence frequency and Agrell's index of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Although some galling species may be found to be more prevalent in urban areas (Frankie et al, 1987), our result is consistent with fi ndings of McGeoch & Chown (1997) and Mingaleva et al (2011), who report an overall reduction in gall infestation rate on seven tree species in urban areas (but these studies did not investigate beech, Fagus sylvatica) and Segebade & Schaefer (1979), who found M. fagi to be completely absent in urban trees. In sycamore trees, our result that leaf gall infestation was highest in low urbanised areas, contrasts previous fi ndings of Skrzypczyńska (2004) and Segebade & Schaefer (1979), who reported higher infestation rates of Aceria cephalonea and Aceria macrorhyncha in urban areas.…”
Section: Effects Of Urbanisation and Forest Size On Plant Gallscontrasting
confidence: 99%
See 1 more Smart Citation
“…Although some galling species may be found to be more prevalent in urban areas (Frankie et al, 1987), our result is consistent with fi ndings of McGeoch & Chown (1997) and Mingaleva et al (2011), who report an overall reduction in gall infestation rate on seven tree species in urban areas (but these studies did not investigate beech, Fagus sylvatica) and Segebade & Schaefer (1979), who found M. fagi to be completely absent in urban trees. In sycamore trees, our result that leaf gall infestation was highest in low urbanised areas, contrasts previous fi ndings of Skrzypczyńska (2004) and Segebade & Schaefer (1979), who reported higher infestation rates of Aceria cephalonea and Aceria macrorhyncha in urban areas.…”
Section: Effects Of Urbanisation and Forest Size On Plant Gallscontrasting
confidence: 99%
“…The few studies investigating the impact of urbanisation on the infestation rates of the plant-galling arthropods yielded contrasting results. McGeoch & Chown (1997) and Mingaleva et al (2011) reported a reduction in infestation rates of galling arthropods with urbanisation, whereas Dreistadt et al (1990) and Sumoski et al (2009) reported positive effects and Skrzypczyńska (2004) found an overall neutral effect of urbanisation.…”
Section: Gall Mortalitymentioning
confidence: 99%
“…Kowalski [27] showed that A. hystrix frequently occurs in necroses associated with Dr. glutinosa galls, and this result was confirmed in the present study. Both gall midges occur throughout most of the distribution range of their host, A. pseudoplatanus, and are serious pests on maple that are capable of causing outbreaks [46,47,76]. Certain species of endophytic fungi that occur in the leaves but are dormant can be stimulated to pathogenic development by the activity of gall insects [77,78].…”
Section: Apiognomonia Hystrix: Host Plant Spectrum and Disease Symptomsmentioning
confidence: 99%
“…The propagules of C. depraedans found in Poland did not differ morphologically from those found in other countries (Redhead 1975;Willetts 1997;Butin 1981b;Wulf 1994). Their presence is essential for the identification of C. depraedans because the lesions are not specific and are very similar to those caused by other fungi or insects and mites causing galls (Kowalski 2003;Skrzypczyńska 2004).…”
Section: Disscusionmentioning
confidence: 99%
“…(Butin 1996;Mańka 2005) or by gall-forming insects and mites, e.g. Harrisomyia vitrina (Kieffer) and Eriophyes pseudoplatani Corti (Skrzypczyńska 2004). The joint action of fungi and gall-forming insects in the development of necroses can make the diagnosis of their causal agents difficult.…”
Section: Introductionmentioning
confidence: 99%